Comment on Covelli et al. Extracorporeal Shock Wave Therapy (ESWT) vs. Exercise in Thumb Osteoarthritis (SWEX-TO): Prospective Clinical Trial at 6 Months. Life 2024, 14, 1453 - Feray Karademir; Tüzün Fírat (Life)
We read the study by Covelli et al [...]